Health and health care access for Syrian refugees living in A degrees stanbul - Torun, PERİHAN; TORUN, PERİHAN; Karaaslan, Meltem Mucaz; Sandikli, BÜŞRA; SANDIKLI, BÜŞRA; ACAR, Ceyda; Shurtleff, Ellyn; Dhrolia, Sophia; HEREK, Bulent (My University, 2018)
The study was conducted to assess the health needs of urban refugees living in A degrees stanbul.